Feasibility of Colocating a Nutrition Education Program into a Medical Clinic Setting to Facilitate Pediatric Obesity Prevention - Mical K. Shilts; L. Karina Diaz Rios; Katherine H. Panarella; Dennis M. Styne; Louise L. Lanoue; Christiana M. Drake; Lenna Ontai; Marilyn S. Townsend (SAGE Publishing, 2021)
Purpose: Within a medical clinic environment, pediatric obesity prevention education for families faces challenges. Existing long-term government-funded nutrition education programs have the expertise and staff to deliver. The purpose is to determine feasibility of colocating the Expanded Food and Nutrition Education Program (EFNEP) into a medical clinic setting to support pediatric obesity prevention. Methods: Physicians from a large university teaching and research hospital (n = 73) and 4 small Medicaid-serving community clinics (n = 18) in the same geographic area in northern California were recruited and trained in the patient-referral protocol for a primary prevention intervention provided by EFNEP. The 8-week intervention deployed in the medical clinics, included general nutrition, physical activity and parenting topics anchored with guided goal setting and motivational modeling. Referral, enrollment, and attendance data were collected for 2 years. Parent and physician feasibility surveys, parent interviews and parent risk assessment tools were administered. Paired-sample t-test analysis was conducted. Results: Twenty intervention series with parents of patients (n = 106) were conducted at 5 clinics. Physicians (n = 92) generated 686 referrals. Every 6 referrals generated 1 enrolled parent. Physicians (91%, n = 34) reported the intervention as useful to families. Parents (n = 82) reported improved child behaviors for sleep, screen time, physical activity, and food and beverage offerings ( P  < .0001) and at family mealtime ( P  < .001). Focus group interviews (n = 26) with 65 participants indicated that parents (97%) reacted positively to participating in the intervention with about a third indicating the classes were relevant to their needs. Conclusion: The intervention is a feasible strategy for the 5 medical clinics. Physicians referred and parents enrolled in the intervention with both physicians and parents indicating positive benefits. Feasibility is contingent upon physician awareness of the intervention and motivation to refer patients and additional EFNEP and clinic staff time to enroll and keep parents engaged.